The TinMan study: feasibility trial of a psychologically informed, audiologist-delivered, manualised intervention for tinnitus. (1st December 2020) - Taylor, John A.; Thompson, Dean M.; Hall, Deborah A.; Walker, Dawn-Marie; McMurran, Mary; Casey, Amanda; Featherstone, Debbie; MacDonald, Carol; Stockdale, David; Hoare, Derek J.
Abstract: Objective: To develop a manualised psychological treatment for tinnitus that could enhance audiologist usual care, and to test feasibility of evaluating it in a randomised controlled trial. Design: Feasibility trial, random allocation of patients to manualised treatment or treatment as usual, and mixed-methods evaluation. Study sample: Senior audiologists, and adults with chronic tinnitus. Results: Recruitment reached 63% after 6 months (feasibility pre-defined as 65%). Only nine patients (47%) were retained for the duration of the trial. Patients reported that the treatment was acceptable and helped reassure them about their tinnitus. Audiologists reported mixed feelings about the kinds of techniques that are presented to them as 'psychologically informed'. Audiologists also reported lacking confidence because the training they had was brief, and stated that more formal supervision would have been helpful to check adherence to the treatment manual. Conclusions: The study indicate potential barriers to audiologist use of the manual, and that a clinical trial of the intervention is not yet feasible. However, positive indications from outcome measures suggest that further development work would be worthwhile. Refinements to the manual are indicated, and training and supervision arrangements to better support audiologists to use the intervention in the clinic are required. Trial Registration: ISRCTN13059163.